IN-VITRO INHIBITION TEST OF SINTRONG LEAVES (CRASSOCEPHALUM CREPIDIOIDES) CRUDE EXTRACT ON EDWARDSIELLA ICTALURI BACTERIA - Nova, Jely; Suprastyani, Heny; Prajitno, Arief (Journal of Environmental Engineering and Sustainable Technology, 2022)
Parasites, viruses, and bacteria contribute to the transmission of infectious diseases. Catfish Enteric Septicemia (ESM) is caused by the bacterium Edwardsiella ictaluri. Antibiotics are used to treat this disease. However, the continuous use of antibiotics will lead to antibiotic resistance in fish and the contamination of the environment. Therefore, it is vital to have an alternative containing natural antibacterial components, such as Sintrong Leaf (Crassocephalum crepidioides). The composition of sintrong leaves consists of flavonoids, alkaloids, saponins, and tannins. This study employed an experimental method with a completely randomized design (CRD), which included five treatments and three replications. Treatment dosages of 25 ppm, 50 ppm, 75 ppm, 100 ppm, and 125 ppm were utilized along with the positive control (doxycycline) and negative control (without treatment). The investigation revealed that a crude extract of sintrong leaf exhibited an inhibitory effect that was effective against E. ictaluri bacteria. The equation pattern indicated y = -0.0004x2 + 0.0716x + 6.933 with an R2 coefficient of 0.71 showing a quadratic graph as the outcome. The graph results show that the best dose of crude extract from sintrong leaves against E. ictaluri bacteria is 89.5 ppm.